The Framework of Factors for the Improvement of the Significant Clauses in the Standard Form of Contract for the IBS Construction Approach in Malaysia - Mohd Fateh, Mohd Ashraf; Mohammad, Mohammad Fadhil (International Journal of Sustainable Construction Engineering and Technology, 2021)
The Industrialised Building System (IBS) was introduced over 10 years ago in Malaysia, with well-documented benefits and strong support from the government. Apparently, the adoption and implementation of IBS is still low and below the government target. When adopting IBS, construction players mostly face different issues and challenges, particularly on contractual aspects, which contribute to the low adoption of IBS in Malaysia. There is also a lack of provision in the significant clauses of the Malaysian standard contract form to fit the development of IBS to date. The aim of this paper is thus to establish a system of factors underpinned by Deming's Theory for the improvement of the significant clauses in the standard contract form for IBS construction in Malaysia. A multi-method approach was used to achieve its aim, including an extensive literature review, findings from the previous study via document analysis, preliminary survey, questionnaire survey and semi-structured interviews. The research revealed that there are five significant clauses with important factors that can be improved in the existing Malaysian standard form of contract in relation to the IBS construction. The research also developed a framework that would be able to assist the policy and decision-makers in understanding what the improvement factors that need to be considered in the significant clauses in the standard form of contract in relation to the IBS construction. The research output (the framework) was validated by the prominent industry players on the practicality, suitability to its purposes for the related stakeholders. The developed framework would be able to accelerate the adoption of IBS construction in parallel with the initiatives (P3) in the Construction Industry Transformation Programme (CITP).